PENGARUH SISTEM REKRUTMEN DAN PENEMPATAN POSISI KARYAWAN TERHADAP MOTIVASI KERJA KARYAWAN PADA HOTEL TAMPIARTO PROBOLINGGO - Mohammad Iskak Elly; Seger Priantono; Reny Augustina (UNEJ e-Proceeding)
The purpose of this study to determine the effect partially, simultaneously or dominant between the system of recruitment and placement of employees on employee motivation in Tampiarto Probolinggo. Sampling was total sampling method. The analytical method used is multiple linear regression analysis. variable recruitment system and variable placement of employees influence partially and simultenously on employee motivation. Variable placement of employees dominantly influence on employee motivation.